2021
DOI: 10.1007/s10803-021-05043-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Electrophysiological Correlates of Working Memory Impairments in Neurofibromatosis Type 1

Abstract: Neurofibromatosis 1 (NF1) is a single gene disorder associated with working Memory (WM) impairments. The aim of this study was to investigate P300 event-related potential (ERP) associated with WM in NF1. Sixteen adolescents with NF1 were compared with controls on measures of WM and EEG was recorded during a WM nback task. The NF1 group showed poorer performance on measures of WM as compared to the control group. No group differences were observed in P300 amplitude at Pz, but P300 latency was shorter in the NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Many studies have identified impairment of executive functions and working memory in patients with NF1 [90]. An increased prevalence of attention deficit hyperactivity disorder (ADHD) in children with NF1 has been reported [91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified impairment of executive functions and working memory in patients with NF1 [90]. An increased prevalence of attention deficit hyperactivity disorder (ADHD) in children with NF1 has been reported [91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a battery of behavioural and cognitive assessments was administered, including parent-rated and cognitive measures that tapped into: overall cognitive function, inattention, hyperactivity, communication, daily living skills, socialisation, short-term memory, working memory, sustained attention, and attentional switching, followed by EEG. This paper focuses on parent-reported 3 Adaptive Behaviour Composite (ABC) scores on the Vineland Adaptive Behaviour Scale (VABS-III) [38], performance on an adaptive auditory n-back task [16], and performance on a non-adaptive visual n-back task [16] performed during EEG (see Pobric et al [16] for details of the other tasks performed that are not reported here).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent analyses were conducted on target and non-target trial data without distinguishing between these conditions, since n-back performance requires maintenance of information during both trial types, particularly in the late post-ERP time window (described below). For the same reason, the number of non-target trials was not decimated to match the number of target trials (which was done in the P300 analysis presented Pobric et al, [16]).…”
Section: Methodsmentioning
confidence: 99%
“…2015 ) with impairments in all aspects of executive function ( Plasschaert et al. 2016 ) including working memory impairments ( Pobric et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%